(untitled) (Journal of the College of Basic Education, 2022)
The school curricula have an effective role in increasing the skills and abilities of students, and they have an important role in the transfer of values. And the desired concepts, because these values ​​cannot be consolidated or transferred to students except through academic curricula. developed and mature, and that each academic course has its own characteristics and objectives, both public and private, and among these curricula Art education curriculum, which is part of the educational process and carries out the task of developing and growing